Genome-wide identification of bHLH transcription factors and their response to salt stress in Cyclocarya paliurus - Zhang, Zijie; Fang, Jie; Zhang, Lei; Jin, Huiyin; Fang, Shengzuo (Frontiers in Plant Science, 2023)
As a highly valued and multiple function tree species, the leaves of Cyclocarya paliurus are enriched in diverse bioactive substances with healthy function. To meet the requirement for its leaf production and medical use, the land with salt stress would be a potential resource for developing C. paliurus plantations due to the limitation of land resources in China. The basic helix-loop-helix (bHLH) transcription factor protein family, the second largest protein family in plants, has been found to play essential roles in the response to multiple abiotic stresses, especially salt stress. However, the bHLH gene family in C.paliurus has not been investigated. In this study, 159 CpbHLH genes were successfully identified from the whole-genome sequence data, and were classified into 26 subfamilies. Meanwhile, the 159 members were also analyzed from the aspects of protein sequences alignment, evolution, motif prediction, promoter cis-acting elements analysis and DNA binging ability. Based on transcriptome profiling under a hydroponic experiment with four salt concentritions, 9 significantly up- or down-regulated genes were screened, while 3 genes associated with salt response were selected in term of the GO annotation results. Totally 12 candidate genes were selected in response to salt stress. Moreover, based on expression analysis of the 12 candidate genes sampled from a pot experiment, CpbHLH36/68/146 were further verified to be involved in the regulation of salt tolerance genes, which is also confirmed by protein interaction network analysis. This study was the first analysis of the transcription factor family at the genome-wide level of C. paliurus, and our findings would not only provide insight into the function of the CpbHLH gene family members involved in salt stress but also drive progress in genetic improvement for the salt tolerance of C. paliurus.